Mesoscale Warm-Core Eddies Drive Interannual Modulations of Swordfish Catch in the Kuroshio Extension System - Durán Gómez, Gloria Silvana; Nagai, Takeyoshi; Yokawa, Kotaro (Frontiers in Marine Science, 2020)
Recent observational and numerical studies have suggested that the decadal modulation of the Kuroshio Extension system, driven by mesoscale variabilities, profoundly affect the basin scale physical and biogeochemical oceanography. However, it remains unclear how these decadal changes affect distribution and abundance of fish species in this region. In this study, 26,964 swordfish catch data obtained by longliners during 2004 and 2010 in the western North Pacific are analyzed with an eddy-resolving ocean reanalysis by using mesoscale dynamic parameters and an eddy detection technique, to clarify the effects of mesoscale eddies and their variabilities on the swordfish catch and distribution. During this period, the Kuroshio Extension underwent two different dynamic phases: stable path state in 2004, 2005 and 2010; and unstable path state during 2006-2009. Based on our analyses, we show here that swordfish are more concentrated in and near the anticyclonic warm-core eddies in the northern site, 36 -45 • N, of the Kuroshio Extension system, especially during the unstable path phase. This is found to be caused by the interannual modulation of mesoscale eddy activities due to more warm-core rings generated from the unstable Kuroshio Extension, making it easier for fishermen to target swordfish in this region.